2012
DOI: 10.1177/0734016811434531
|View full text |Cite
|
Sign up to set email alerts
|

Cliqued Up

Abstract: This study examines the interrelationship between gang affiliation and commitment for a gang-related homicide on the postincarceration recidivism of a sample of 1,804 serious and violent delinquents released from a large southern juvenile correctional system. Controlling for a battery of preincarceration youth characteristics, delinquent background, and social history measures, this research revealed that gang murderers—gang-affiliated offenders committed for a gang-related homicide—were more likely to experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The finding that JHO participants in this study who served less time (8.5 years or less) were more likely to reoffend than those who served longer sentences (15 years or more) makes sense and is consistent with previous research Trulson et al, 2016). Scientific advances have indicated that the adolescent brain does not mature until individuals are about 25 years old (Garbarino, 2018).…”
Section: Juveniles Are Different From Adultssupporting
confidence: 89%
See 3 more Smart Citations
“…The finding that JHO participants in this study who served less time (8.5 years or less) were more likely to reoffend than those who served longer sentences (15 years or more) makes sense and is consistent with previous research Trulson et al, 2016). Scientific advances have indicated that the adolescent brain does not mature until individuals are about 25 years old (Garbarino, 2018).…”
Section: Juveniles Are Different From Adultssupporting
confidence: 89%
“…Several significant predictors of recidivism were identified after five years, including relationships with delinquent friends, number of previous offenses, age at first arrest, and age at homicide. Trulson et al (2012) examined the interrelationship between gang affiliation and commitment for a gang-related murder on the recidivism of 1804 male serious and violent delinquents confined in a southern correctional facility.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical case studies most likely overstate the role of mental health in juvenile homicide, lack of comparison groups prevents the ability to elucidate causes of homicide or whether risk factors of homicide differ from those of other offenses, and retrospective studies lend themselves to bias wherein the outcome (homicide offending) is known leading to incomplete or inaccurate recall of self-reported or parent-reported risks [8]. Some prior work has focused on subsequent recidivism among juveniles who have already committed homicide offenses (see References [10,11,12]). However, there is a notable dearth of research on the prospective prediction of a juvenile’s initial homicide arrest.…”
Section: Introductionmentioning
confidence: 99%